Parenthood From Biology to Relation. Prevention, Assessment and Interventions for Developmental and Clinical Issues - Alessandra Simonelli (Frontiers Research Topics, 2018)
Parenthood represents a fundamental construct that identifies the quality of early adult-infant interactions. In both short and long period, relationships, as primary interactional experiences, have an essential role in influencing individual's adjustment and psychopathology development during in lifetime. In this scenario, the most important areas of interest and innovation are (a) parents' representation of themselves, both in relation to the child and to their care-giving role; (b) the quality of couple relationship, in terms of both conjugal and co-parental bounds, and its influence on the quality of early mother-father-child interactions; (c) the early models of caregiver-baby interaction; (d) the recent approach to the "maternal brain", that represents the contribution coming from neurosciences, linked to the adult's activation and cerebral functioning processes, in association with the parental role. These data are a starting point for the individuation of functioning mechanisms and developmental trajectories of parenting in groups of adults and babies, belonging to normative populations. At the same time, those studies may provide an important introduction to the detection of critical and/or dysfunctional aspects in populations of babies and adults at risk (e.g. preterm babies, adopted children, etc.) or in adults' clinical group (e.g. a depressed parents, addicted parents, etc.) or in children with one or more impaired characteristic (e.g. children with organic diseases, with autistic disorders, etc.).. The present Research Topic puts the attention on these themes, particularly, considering the possible aftermaths that empirical research may have on planning and realizing interventional models to support the parental functioning. We will consider papers focused on the individuation of methods of observation and assessment, which allow to plan and realize prevention programs and/or interventions, primarily focused on parental support, both in the early stadium of the child's development and in the long-term period. Thus, the focus is both on the prevention and sustenance sphere and, also, on specific manners of taking on the therapeutic responsibility of the adult-infant relationship.